Discourses on the edges of life - Salvador, Vicent; Kotátková, Adéla; Clemente, Ignasi (IVITRA research in linguistics and literature, 2020)
"Death inhabits our collective imaginary, even though sometimes, like a squatter, it hides discretely in order to avoid conflicts. It is undoubtedly a multi-faceted subject of study, which requires consideration from an interdisciplinary perspective. This book deals with this phenomenon, and more specifically with the discourses that surround -and construct our perspectives and understanding of- death and dying. Of course, the present volume does not attempt to be exhaustive, and considers the subject from several standpoints, including linguistics, anthropology, history of medicine, and importantly, literary studies. It combines various points of view and different methodologies of knowledge, in the hope that they come together to constitute a written dialogue -or more precisely, a polylogue. The ordering of the texts in this volume provides readers with an itinerary that begins with more general approaches, such as a historical presentation of the medicalisation of death and an in-depth reflection on the best way to die, and ends with studies of specific literary works from different periods. The itinerary that this book provides is framed by a discourse analysis-based overview that explores how different approaches to death and dying intersect and complement each other in an interdisciplinary endeavour. This analysis focuses on literary and non-literary genres in order to shed some new light on a topic that is inexhaustible because of its sociocultural relevance"--